Product Pricing, Accounting Costs and Use of Product-Costing System. - Hilton, Ronald W.; Swieringa, Robert J.; Turner, Martha J. (The Accounting Review, 1988)
The economic theory of the firm suggests that a profit-maximizing product price may be determined by equating marginal cost and marginal revenue. Yet recent surveys suggest that most firms use cost-based pricing strategies where product costs are determined using absorption costing. Lere [1986] has drawn upon the economic theory of the firm, as well as extensive work on heuristic decision processes, to develop an empirically testable theory of product pricing based on accounting costs. This paper reports the results of an experiment in which Lere's theory was empirically tested.